Application of a light-enhanced carbon nitride homojunction electrode in light-assisted rapid detection of highly toxic hexavalent chromium
By using light-enhanced carbon nitride homojunction electrode in electrochemical sensors, using its electron-hole pair catalytic reaction under light irradiation, the problems of high limit and insufficient sensitivity of hexavalent chromium detection in the prior art are solved, and high sensitivity and low cost detection effects are achieved.
Patent Information
- Application Number
- CN202411803164.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-10
AI Technical Summary
When detecting highly toxic hexavalent chromium, the detection limit is high, the sensitivity is insufficient, the preparation process is complex, and the cost is high.
A photo-enhanced carbon nitride homojunction electrode is used to form a working electrode by loading carbon nitride homojunction nanocomposites on a conductive substrate to prepare an electrochemical sensor. The electron-hole pair generated by this electrode under light irradiation can catalyze redox reactions and improve detection sensitivity.
High sensitivity detection of hexavalent chromium is achieved, the detection limit is reduced to 3.4 nM, and the preparation method is simple, low cost and easy to operate.
Smart Images

Figure CN119290989B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photoelectric active materials and photoelectric sensing analysis, and specifically relates to a light-enhanced carbon nitride homojunction electrode and an electrochemical sensor and applications thereof in detecting highly toxic hexavalent chromium. Background Art
[0002] The photoelectrochemical process involves semiconductor materials, molecules or particles absorbing photons and exciting electrons, thereby generating charge transfer and realizing the conversion of light energy into electrical energy. When the energy of the incident light is equal to or greater than the band gap energy of the semiconductor, the electrons in the valence band are excited to jump to the conduction band, leaving holes in the valence band. This technology relies on the unique photoelectric properties of the material to detect the changes in electrochemical signals caused by light excitation, and then accurately measures the mass of the substance to be measured and other related parameters, and has received widespread attention.
[0003] Electrochemical sensors are sensors that use chemical reactions to generate electrical signals. They are simple to prepare, easy to operate, and low in cost. They have been shown to have high accuracy and low detection limits in heavy metal ion detection. However, the working electrode, as the core component of the electrochemical sensor, determines the sensor's sensing performance, such as detection limit, stability, sensitivity, and linear range.
[0004] The Chinese patent with application number 202310697965.X discloses a Z-type heterojunction composite material, its preparation method and application. It prepares a 2DTiO2@C / Au / 3DBiOIZ-type heterojunction composite material, which is constructed into a photoelectrochemical sensor, and the photoelectrochemical response of the photoelectrochemical sensor to hexavalent chromium ions is used to detect the concentration of hexavalent chromium ions. The preparation process of the heterojunction composite material in this method is complicated, and precious metals are required, which is costly. In addition, its detection limit is 6nM, and the sensitivity still needs to be improved.
[0005] Therefore, finding a working electrode material with high electrochemical activity, good dispersibility and long-term stability is of utmost importance to obtain a stable and efficient electrochemical sensor for detecting highly toxic hexavalent chromium. Summary of the invention
[0006] In view of the shortcomings and deficiencies of the above-mentioned prior art, the primary purpose of the present invention is to provide a light-enhanced carbon nitride homojunction electrode, in which the carbon nitride homojunction nanocomposite (electrode material layer) serves as a catalyst, and the electron-hole pairs generated under light irradiation can catalyze redox reactions, thereby improving the detection sensitivity.
[0007] Another object of the present invention is to provide an electrochemical sensor, which consists of a working electrode, a counter electrode, a reference electrode, an electrolytic cell and an electrochemical workstation, wherein the working electrode consists of a conductive substrate and a sensor material layer loaded on the substrate.
[0008] Another object of the present invention is to provide applications of the above-mentioned electrode and electrochemical sensor.
[0009] The present invention is as follows through the following technical solutions:
[0010] A light-enhanced carbon nitride homojunction electrode is used in light-assisted rapid detection of highly toxic hexavalent chromium. Urea and melamine are mixed and dissolved in water, and a mixed solution is obtained by sufficient stirring. The obtained mixed solution is dried and calcined at a high temperature of 400-550°C for 1-5 hours. The obtained solid is cooled and then further ground into powder to obtain a carbon nitride homojunction nanocomposite. The carbon nitride homojunction nanocomposite is loaded on a conductive substrate to form a working electrode for preparing an electrochemical sensor.
[0011] Preferably, the mass ratio of the urea to melamine is 10±5:20±5, and the mass volume ratio of the urea to water is 0.1:10-50 g / mL.
[0012] Preferably, the stirring time of the mixed solution is 12 to 24 hours; the drying temperature of the mixed solution is 60 to 90° C., and the drying time is 24 to 48 hours.
[0013] Preferably, the calcination conditions are: calcining in a muffle furnace at a high temperature of 450-500° C. with a temperature program of 2-10° C. / min for 2-4 h.
[0014] Preferably, the electrode is prepared by dispersing the carbon nitride homojunction nanocomposite in an ethanol-water mixed solution at a solid-liquid ratio of 0.5 to 4 mg / mL, then adding a Nafion solution, ultrasonically dispersing to obtain a suspension, coating the suspension on the surface of a conductive substrate, and drying to obtain an electrode.
[0015] Preferably, the volume ratio of ethanol to water in the ethanol-water mixed solution is 1:1-8; and the volume mass ratio of the Nafion solution to the carbon nitride homojunction nanocomposite is 10-50 μL / mg.
[0016] Preferably, the ultrasonic dispersion has a power of 50-100 W and a time of 0.5-2 h.
[0017] Preferably, the suspension is coated at 40-150 μL / cm 2 The amount of the coating is coated on the surface of the conductive substrate, and the more preferred amount is 50-100 μL / cm 2 ; The conductive substrate is one of an (L-shaped) glassy carbon electrode, a conductive glass and a carbon cloth electrode.
[0018] The electrochemical sensor comprises the above-mentioned light-enhanced carbon nitride homojunction electrode (working electrode), a counter electrode, a reference electrode, an electrolytic cell and an electrochemical workstation.
[0019] Application of the electrode or electrochemical sensor in light-assisted rapid detection of highly toxic hexavalent chromium. Preferably, a PBS solution with a pH of 4 to 6 is used as the electrolyte, and the concentration is 1.0±0.5 mol / L.
[0020] The carbon nitride homojunction of the present invention, as an efficient photoelectric catalyst, exhibits unique advantages in this process, including: the internal structure of the carbon nitride homojunction is conducive to promoting the effective separation of photogenerated electrons and holes, reducing the recombination probability between them, and significantly improving the photoelectric conversion efficiency; the carbon nitride homojunction can absorb a wider range of solar spectrum regions, increase the available energy range, and promote more redox reactions. In specific applications, such as the detection of hexavalent chromium (Cr(VI)), the carbon nitride homojunction plays an important role. By placing a sample containing Cr(VI) on the surface of the carbon nitride homojunction and applying appropriate lighting conditions, a series of photoelectrochemical reactions can be induced. In this process, Cr(VI) is reduced to a lower valence form, and the carbon nitride homojunction acts as a medium to promote this reduction reaction. As the reaction proceeds, the resulting current or voltage changes can directly reflect the presence of Cr(VI) and its concentration level, providing a fast and sensitive method for environmental monitoring. Therefore, the carbon nitride homojunction-based photoelectrochemical detection technology not only demonstrates its potential in improving the photoelectric conversion efficiency, but also proves its important value as an efficient analytical tool in the detection of harmful substances such as hexavalent chromium.
[0021] The present invention makes an electrode based on the photocatalytic activity and electrochemical performance of a carbon nitride homojunction, which can achieve effective and sensitive detection of hexavalent chromium. In the homojunction structure, two identical carbon nitride layers are coupled through the interface to form an enhanced photogenerated carrier separation mechanism, which can improve the photoelectric conversion efficiency and stability. When such a homojunction is made into an electrode or a photoelectrochemical sensor, the electron-hole pairs generated under light irradiation can catalyze redox reactions, such as the reduction of hexavalent chromium. Differential pulse voltammetry is a commonly used electrochemical technique for detecting low concentrations of analytes. It superimposes a series of small-amplitude, low-frequency voltage pulses on the substrate potential and measures the resulting current response. When detecting hexavalent chromium, when the sample solution contains hexavalent chromium, it will be reduced to trivalent chromium on the electrode surface, and this process is accompanied by electron transfer. Through differential pulse voltammetry, the current change of this electron transfer can be accurately measured, thereby improving the detection sensitivity and being able to quickly and quantitatively analyze the concentration of hexavalent chromium.
[0022] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0023] (1) The carbon nitride homojunction nanocomposite prepared by the present invention has excellent optical properties as an electrode material layer. The prepared carbon nitride homojunction electrode has excellent differential pulse voltammetry detection signals under visible light conditions. The strong redox property of the electron-hole pairs generated by the semiconductor material under light can improve the sensitivity of sensor detection. For example, the detection limit of hexavalent chromium is as low as 3.4 nM.
[0024] (2) The preparation method of the carbon nitride homojunction nanocomposite of the present invention is simple, and the raw material price is low, which greatly reduces the cost of the electrode. In addition, the preparation process of the entire sensor is simple and easy to operate, does not require reliance on large-scale instruments and equipment, and can achieve rapid detection. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 TEM morphology of the carbon nitride homojunction prepared in Example 1 (a); XRD spectrum of the carbon nitride homojunction and carbon nitride (b).
[0026] Figure 2 The peak current influence curve of the differential pulse voltammetry curve of the light-enhanced carbon nitride homojunction electrode detecting hexavalent chromium in different pH buffer solutions in Example 1.
[0027] Figure 3 The peak current influence curve of the differential pulse voltammetry curve of hexavalent chromium detected by the light-enhanced carbon nitride homojunction electrode with different coating amounts of carbon nitride homojunction suspension in Example 1.
[0028] Figure 4 Detection of carbon nitride electrodes and carbon nitride homojunction electrodes under light and no light conditions 10 -6 Differential pulse voltammetry curve of mol / L hexavalent chromium.
[0029] Figure 5 Detection of carbon nitride electrodes and carbon nitride homojunction electrodes under light and no light conditions 10 -6 mol / L hexavalent chromium cyclic voltammetry curve.
[0030] Figure 6 The carbon nitride homojunction electrode at different scan rates at 10 -6 Cyclic voltammetry curves (a) and their linear relationship (b) in a mol / L hexavalent chromium solution under visible light irradiation.
[0031] Figure 7 The differential pulse voltammetry curves (a) and their linear relationship (b) of the carbon nitride homojunction electrode under visible light irradiation in solutions with different hexavalent chromium concentrations.
[0032] Figure 8 This is a test diagram of the reusability performance of carbon nitride homojunction electrodes. DETAILED DESCRIPTION
[0033] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0034] The carbon nitride homojunction involved in the embodiment of the present invention is prepared by the following steps:
[0035] (1) A certain amount of urea and melamine are mixed and dissolved in a certain amount of deionized water, and stirred to obtain a fully mixed solution. The obtained mixed solution is placed in an oven and dried overnight to construct a composite material. The composite material is transferred to a quartz crucible and calcined in a muffle furnace at a high temperature with a temperature increase program of 2°C / min for a certain time. The obtained light yellow solid is cooled to room temperature and then further ground into powder to obtain a carbon nitride homojunction nanocomposite.
[0036] (2) The carbon nitride homojunction nanocomposite is dispersed in a mixed solution of ethanol and water at a solid-liquid ratio of 0.5 to 4 mg / mL, and then a Nafion solution is added to obtain a suspension after ultrasonic dispersion. The suspension is coated on the surface of a conductive substrate and naturally dried to obtain a carbon nitride homojunction electrochemical sensor, namely, the light-enhanced electrochemical sensor.
[0037] The room temperature described in the present invention is 20-30°C.
[0038] Example 1
[0039] (1) 0.1 g of urea and 0.4 g of melamine were mixed and dissolved in 30 mL of deionized water, and stirred for 24 h to obtain a fully mixed solution. The obtained mixed solution was placed in a 90 °C oven overnight (12 h) to dry to obtain a composite material. The composite material was transferred to a quartz crucible and calcined in a muffle furnace at 500 °C for 2 h with a heating program of 2 °C / min. The obtained light yellow solid was cooled to room temperature and then further ground into powder to obtain a carbon nitride homojunction (nanocomposite).
[0040] (2) 1 mg of the prepared carbon nitride homojunction (nanocomposite) was dispersed in 1 mL of a mixed solution of water and ethanol in a volume ratio of 2:1, 20 μL of a 5% mass concentration Nafion solution was added, and ultrasonic dispersion was performed for 0.5 h to obtain a uniform light yellow suspension. 3 μL of the suspension was taken with a 10 μL micro-pipette and dropped on the surface of a glassy carbon electrode (3 mm in diameter), and naturally dried at room temperature to obtain the carbon nitride homojunction working electrode.
[0041] In Example 1, the carbon nitride homojunction TEM morphology and XRD spectrum are shown in Figure 1 ,Depend on Figure 1a It can be seen that the carbon nitride homojunction has a larger specific surface area and the sample surface has more wrinkles, which is more conducive to the reaction. Figure 1 b As can be seen, all prepared samples show two obvious diffraction peaks, which correspond to the standard card of carbon nitride (JCPDS, No.87-1526). On the one hand, the peak observed at a lower diffraction angle of 13.4° corresponds to the (100) crystal plane. On the other hand, there is a more obvious peak at about 27.4° that can be indexed to the (002) crystal plane. It should be noted that all samples show the same XRD trend. This indicates that the carbon nitride homojunction has not changed its basic crystal layout, which is consistent with the TEM image.
[0042] The application of the electrode prepared in Example 1 in the detection of highly toxic hexavalent chromium under light conditions is as follows: The detection is carried out in a traditional three-electrode system, using a platinum wire electrode as a counter electrode, silver / silver chloride as a reference electrode, and using the working electrode prepared in Example 1, containing 10 -6 1 mol / L PBS buffer with different pH values of hexavalent chromium was used as the electrolyte solution, and an electrochemical workstation was used as the detection instrument. The working electrode was first polished on α-alumina polishing powder with a particle size of 50 nm, and then ultrasonically washed with deionized water and anhydrous ethanol in turn. The light intensity was 100 mW / cm 2 In the process of detecting hexavalent chromium, the carbon nitride homojunction electrochemical sensor uses differential pulse voltammetry to scan the redox reaction of hexavalent chromium and record the voltage-current curve of this process.
[0043] Based on the above steps, Figure 2 ,from Figure 2 It can be seen that the current density of hexavalent chromium detected by differential pulse voltammetry is significantly affected by the pH value of the PBS buffer solution. When the pH is acidic or weakly acidic, the current density of differential pulse voltammetry is much larger than that of alkaline solution. This may be because when hexavalent chromium is mainly in the form of HCrO4 in acidic solution, - 、CrO4 2- and Cr2O7 2- , rich in H + The presence of is beneficial to the reduction of hexavalent chromium, while OH - The presence of will inhibit it. Therefore, the acidic PBS buffer solution with pH = 5 is more conducive to the photoelectrochemical detection of hexavalent chromium.
[0044] Figure 3 The three-electrode system detected 10 in 1 mol / L PBS buffer (pH=5) using sensors prepared by different drop volumes of carbon nitride homojunction (catalyst) under illumination. -6 The differential pulse voltammetry curve of mol / L hexavalent chromium. The specific detection steps are the same as above. Figure 3 It can be seen from the figure that when the volume of the catalyst on the electrode gradually increases, the differential pulse voltammetry response signal of the carbon nitride homojunction electrode shows a phenomenon of first increasing and then decreasing. Therefore, the optimal catalyst volume is 5 µL.
[0045] Figure 4 For glassy carbon electrode (GCE), carbon nitride electrode and carbon nitride homojunction electrode at 10 -6 The differential pulse voltammetry curves of M hexavalent chromium + 1mol / L PBS (pH=5) solution under dark conditions and visible light irradiation. The specific detection steps are: in a three-electrode system, a platinum wire electrode is used as the counter electrode, silver / silver chloride is used as the reference electrode, a glassy carbon electrode, a working electrode made of dropwise carbon nitride and a carbon nitride homojunction, containing 10 -6 1 mol / L hexavalent chromium in 1 mol / L PBS buffer was used as the electrolyte solution, and the electrochemical workstation was used as the detection instrument, and the differential pulse voltammetry potential scanning detection was performed. Figure 4 It can be seen that the GCE electrode alone has no response to hexavalent chromium, and the prepared modified electrode has an obvious hexavalent chromium detection peak at around 0.015V. The carbon nitride homojunction electrode shows the largest detection peak current (26.1 µA) when detecting hexavalent chromium under visible light irradiation, which is 1.74 times the peak current of the carbon nitride electrode when detecting hexavalent chromium under dark conditions. In addition, the performance of pure carbon nitride in detecting hexavalent chromium was also tested. The peak current of the pure carbon nitride electrode under visible light irradiation is significantly lower than the signal of the carbon nitride homojunction electrode detecting hexavalent chromium under the same conditions. These phenomena may be attributed to the excellent separation efficiency of photogenerated carriers of the carbon nitride homojunction, so the carbon nitride homojunction electrode has an excellent differential pulse voltammetry detection signal under visible light conditions.
[0046] Depend on Figure 5 It can be seen that the cyclic voltammetry curve of the glassy carbon electrode has no obvious response peak, which may be because the glassy carbon working electrode alone does not have the performance of detecting hexavalent chromium. For the working electrode of the present invention, a pair of redox peaks appear at about 0.2 V, which may be because hexavalent chromium is first adsorbed on the surface of the modified electrode and then reduced to trivalent chromium. In this detection process, the redox peak of the carbon nitride homojunction working electrode under visible light irradiation is the most significant, which also proves that visible light irradiation is conducive to the detection of hexavalent chromium.
[0047] Depend on Figure 6 It can be seen that the oxidation and reduction peaks of hexavalent chromium increase with the increase of scanning rate, and the peak currents of the oxidation peak and the reduction peak are linearly related to the scanning rate, with correlation coefficients of 0.99, indicating that the detection of hexavalent chromium by the carbon nitride homojunction working electrode under visible light irradiation is a surface-controlled electrochemical process.
[0048] Figure 7The following are differential pulse voltammetry curves of carbon nitride homojunction electrode for the detection of different concentrations of hexavalent chromium under visible light irradiation. The specific detection steps are: in a three-electrode system, a platinum wire electrode is used as the counter electrode, silver / silver chloride is used as the reference electrode, a glassy carbon electrode, a working electrode made of dropwise carbon nitride and a carbon nitride homojunction, and a 1 mol / L PBS buffer (pH=5) containing different concentrations (0-1000nmol / L) of hexavalent chromium is used as the electrolyte solution, and an electrochemical workstation is used as the detection instrument, and differential pulse voltammetry potential scanning detection is performed. Figure 7 a is the differential pulse voltammetric response peak of the carbon nitride homojunction electrode for hexavalent chromium reduction, which exhibits a stable and clear response. The peak current of the detection peak also gradually increases with the increase of the concentration of hexavalent chromium, showing different linear relationships in different concentration ranges. Figure 7 b is the linear relationship diagram of the peak current of the differential pulse voltammetry curve corresponding to different concentrations of hexavalent chromium. The linear regression equation of hexavalent chromium is I1=1.49+0.097C(R 2 =0.93), I2=-3.34+0.112C (R 2 =0.98) and I3=19.2+0.007C (R 2 =0.94); where C (n mol / L) is the concentration of hexavalent chromium, and I (μA) is the peak current at different concentrations. Based on the signal-to-noise ratio S / N=3 of hexavalent chromium ion detection as the detection limit standard, it is calculated by the following formula:
[0049] Detection limit = 3.3σ / S
[0050] Where σ is the noise standard deviation of the blank sample response, and S is the slope of the calibration curve, that is, the rate of change of the response signal of the substance to be tested as its concentration increases. S is the slope of I1, σ=0.099, and the test result is calculated according to the formula. The detection limit of hexavalent chromium is 3.4 nM.
[0051] Depend on Figure 8 It can be seen that after 100 consecutive operations using the same electrode, the peak current of hexavalent chromium shows a slight decrease. Therefore, the carbon nitride homojunction working electrode has good cyclic performance.
[0052] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. Application of a light-enhanced carbon nitride homojunction electrode in light-assisted rapid detection of highly toxic hexavalent chromium, characterized in that: The urea and melamine are mixed and dissolved in water, and the mixed solution is fully stirred to obtain a mixed solution, the mixed solution is dried, and calcined at a high temperature of 400-550° C. for 1-5 hours, the obtained solid is cooled, and then further ground into powder to obtain a carbon nitride homojunction nanocomposite; the carbon nitride homojunction nanocomposite is loaded on a conductive substrate to prepare an electrode; The mass ratio of the urea to melamine is 10±5:20±5, and the mass volume ratio of the urea to water is 0.1:10-50 g / mL.
2. The use according to claim 1, characterized in that: The stirring time of the mixed solution is 12 to 24 hours; the drying temperature of the mixed solution is 60 to 90° C., and the drying time is 24 to 48 hours.
3. The use according to claim 2, characterized in that: The calcination conditions are: calcining in a muffle furnace at a high temperature of 450-500° C. with a temperature increase of 2-10° C. / min for 2-4 hours.
4. The use according to claim 3, characterized in that: Preparation of the electrode: dispersing the carbon nitride homojunction nanocomposite in a mixed solution of ethanol and water at a solid-liquid ratio of 0.5 to 4 mg / mL, then adding Nafion solution, obtaining a suspension after ultrasonic dispersion, coating the suspension on the surface of a conductive substrate, and obtaining an electrode after drying.
5. The use according to claim 4, characterized in that: The volume ratio of ethanol to water in the ethanol-water mixed solution is 1:1-8; the volume mass ratio of the Nafion solution to the carbon nitride homojunction nanocomposite is 10-50 μL / mg.
6. The use according to claim 5, characterized in that: The power of the ultrasonic dispersion is 50-100 W, and the time is 0.5-2 h; the suspension is coated with 40-150 μL / cm 2 The amount is coated on the surface of the conductive substrate.
7. The use according to claim 6, characterized in that: The suspension is coated with 50-100 μL / cm 2 The amount is coated on the surface of the conductive substrate.
8. The use according to claim 7, characterized in that: The conductive substrate is one of a glassy carbon electrode, a conductive glass and a carbon cloth electrode.
9. The use according to any one of claims 1 to 8, characterized in that: The electrode was used as a working electrode to prepare an electrochemical sensor, and a PBS buffer solution with a pH of 4 to 6 was used as an electrolyte for detection.
Citation Information
Patent Citations
Z-type heterojunction composite material and preparation method and application thereof
CN117816955A
3D defect carbon nitride photocatalytic material, and preparation method and application thereof
CN111215116A